Daredevil. Cold day in Hell - Soule, Charles; McNiven, Steve (Daredevil, 2026)
"Years into the future, a powerless Matt Murdock is no longer Daredevil - but he's still the Man Without Fear! The stellar creative team of DEATH OF WOLVERINE reunites for a bold future vision of Daredevil, introducing a grizzled, older version of Matt Murdock! Matt may no longer have his incredible abilities, but he's still doing whatever he can to help those in need in a city broken beyond repair. And he'll finally be able take the fight to where it matters most when catastrophe strikes, causing his powers to miraculously return. With no one by his side, Daredevil has little chance against the evil permeating every corner - until Captain America entrusts him with a mission to safeguard the world's only hope!"--Amazon.